Multi-cultural management, work and organizational differences. - Mahamud, Tosaporn (Journal of Management Science Nakhon Pathom Rajabhat University, 2020)
Cultural diversity In the workplace grow According to the path In the past, progress Of the modern world Until the work of the staff There are differences That culture And will have different ways of thinking Causing problems in work The purpose of this study To create ideas In the way of working together Effectively Working in a multinational company with rules from the parent company Regarding cultural differences Cultural dimension organizational culture In order to be a study guide to reduce problems in work including the context for cross-cultural communication and can use the method of kicking from the content to Take advantage that Occur in the organization effectively Article history: Received 6 August 2019 Revised 20 September 2019 Accepted 23 September 2019 SIMILARITY INDEX = 0.00 %